Communicating Biophilic Design: Start With the Grasslands - Marshall, Adrian J.; Williams, Nicholas S. G. (Frontiers in Built Environment, 2019)
To protect remnant ecosystems within urban areas, guidelines are needed for the biophilic design, construction, and ongoing occupation of the suburban subdivisions, industrial land, or business parks surrounding them. Planners, urban designers, architects, landscape architects, road engineers, and the community need tools to help design and manage urban landscapes in a way that puts the ecosystem's requirements on par with urban development. The Victorian National Parks Association recognized this need and developed Start with the grasslands (SWTG) as a set of biophilic urban design guidelines to protect remnant grasslands within urban areas. South-eastern Australia's grasslands are Australia's most endangered ecosystem, with <2% remaining. Many are within or at the fringes of urban areas and are in continuing decline in extent and quality. Because of considerable challenges to acceptance, the development of these biophilic design guidelines was as important as the guidelines themselves. The process was structured to maximize inclusivity and stakeholder buy-in, educate, shift debate from traditional lines of argument, and to communicate the complex relationships to be negotiated for a successful outcome. The guidelines needed to be evidence-based, trans-disciplinary, and refer directly to on-the-ground case studies. Organizational partnerships further built legitimacy. Recommendations span spatial scales from the highly local to the regional and consider the full timescale of urban development. SWTG communicates through non-confrontational language and visual techniques.